2015
DOI: 10.1007/s10661-015-4453-2
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of long-term intensive agriculture on the Vertisol properties in a calcareous region

Abstract: Morphological, physicochemical, and mineralogical properties of Vertisols (Chromic Calcixererts, Typic Haploxererts, and Typic Calcixererts) influenced under farming practices and adjoining uncultivated soils were investigated in order to contribute to the understanding of changes derived by intensive cultivation (over five decades). The study revealed that A-horizon thickness enhanced from 20 cm in the uncultivated soil to 30 cm in the cultivated soil for Typic Haploxererts and Typic Calcixererts. Under cropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Classification systems that function like the LSRS can track soil quality following disturbance and provide objective evidence of recovery. A land productivity index applied in central Iran found that two groups of Vertisols displayed reduced productivity indices while a third group showed an improved index in response to the long-term effects of cropping practices (Rezapour et al, 2015). Three of five reclaimed coal mine sites in the semi-arid western United States had higher land capability compared to references while two of five had reduced land capability (Schafer, 1984).…”
Section: Land Capabilitymentioning
confidence: 99%
“…Classification systems that function like the LSRS can track soil quality following disturbance and provide objective evidence of recovery. A land productivity index applied in central Iran found that two groups of Vertisols displayed reduced productivity indices while a third group showed an improved index in response to the long-term effects of cropping practices (Rezapour et al, 2015). Three of five reclaimed coal mine sites in the semi-arid western United States had higher land capability compared to references while two of five had reduced land capability (Schafer, 1984).…”
Section: Land Capabilitymentioning
confidence: 99%
“…Faktor teknologi dapat menyebabkan degenerasi agroekosistem seperti penggunaan bahan kimia dan pengolahan tanah yang tidak ramah lingkungan, sistem monokultur jangka panjang tanpa rotasi, serta kurangnya pengembangan dan penataan varietas atau klon. Pertanian monokultur intensif (pengolahan tanah dan input) dan terus-menerus dalam jangka panjang akan menunjukkan keadaan agroekosistem degeneratif sebagai akibat dari penurunan kualitas lahan seperti penurunan kandungan bahan organik, kation terlarut, dan kapasitas tukar kation (Rezapour et al 2015). Pertanaman kentang intensif yang terus-menerus dalam jangka panjang menunjukkan penurunan produktivitas seperti dilaporkan oleh Saini dan Grant (1980) antara lain akibat erosi yang tinggi jika guludan searah kelerengan (Henny et al 2011).…”
Section: Faktor Regeneratif -Degeneratifunclassified
“…Land productivity is the term given to the capability of land to perform productivity potential based on an evaluation of its physical, chemical, and biological characteristics. This index is greatly important in the management decisions on to accept a type and intensity of land use permanently without long-time degradation (Rezapour et al 2015).…”
Section: Land Productivity Index (Lpi)mentioning
confidence: 99%